Changes of Strategic Pricing Policy of Logistics Service Providers in Financial Macroeconomic Instability - Simek, Libor; Cempirek, Vaclav; David, Andrej; Galierikova, Andrea (Asian Economic and Financial Review, 2021)
This paper aims to examine the influence of macroeconomic instability on the microeconomic environment, especially on financial strategy after the application of strategic pricing policy by providers of logistics services and make recommendations for providers who use pricing as a marketing tool. Special attention is paid to enhancing their competitive position in times of economic crisis. The research is based on an analysis of the situation during the 2008–2009 economic crisis. It is hypothesized that the number of providers who applied a strategic pricing policy after its culmination in 2010 was higher than in 2008 (shortly before the onset of the crisis). The conclusions derived are then transferred to the period of the 2020 coronavirus economic recession under the assumption of the same analogical characteristics of both periods. The paper does not speculate – its purpose is to present a thorough and complex analysis of the situation by employing a wide range of statistical instruments, thereby attaining results of a very high level of statistical reliability. The study has the potential to be a valuable contribution to the literature in its respective field, especially during global anti-Covid measures, which makes the theme of strengthening competitive positions of logistics service providers very topical.